Rehabilitation therapy effect on state of hemodynamic of the head and neck vessels in children with cervicogenic headache - Korolenko, N. V.; Gorsha, O. V. (Journal of Education, Health and Sport, 2017)
The purpose of research was follow-up studying (before the treatment course, after the course and 1 and 6 months after the treatment course) of clinical effect of single and combined usage of kinesio taping and physical therapy exercises and their influence on the state of vertebrobasilar basin vascular hemodynamics in the children of younger school age suffering from cervicogenic headache against a background of cervical spine instability.Each of the esamined methods of rehabilitation therapy results in positive dynamics of almost all the values of examination and improves the clinical state (reduction of frequency and intensity of headache), verterobasilar basin vascular hemodynamics (blood flow, vascular elasticity, reaction to the negative extravasal influencing of surrounding structures, venous outflow).The combined usage of kinesio taping and physical therapy exercises renders the best and more long-term clinical effect (such as reduction of frequency and intensity of headache) in children suffering from cervicogenic headache.The comparison of values of vertebrobasilar basin vascular hemodynamics revealed that all the suggested complexes of rehabilitation treatment improved blood flow of both intracranial and extracranial departments of both spine arteries of child patients, however, usage of only physical therapy exercises resulted in the less pronounced dynamics of values as compared with the usage of only kinesio taping and the combined usage of kinesio taping and physical therapy exercises. In case of the combined usage of kinesio taping and physical therapy exercises the reached immediately after the treatment of reduction of asymmetry of intracranial bloodflow persisted for a month, which was not observed in case of usage of other methods of rehabilitation therapy. The examined methods of rehabilitation treatment also resulted in the identical outflow of blood in both eye veins and the better blood outflow by straight sinus in case of the combined usage of kinesio taping and physical therapy exercises in the child patients.